DETEKSI TUMPAHAN MINYAK MENGGUNAKAN METODE ADAPTIVE THRESHOLD PADA CITRA SATELIT SENTINEL-1A DI PERAIRAN UTARA KARAWANG - David Situmorang; Jonson Lumban-Gaol; Efendy Tambunan (UKI Press, 2025)
The North Karawang Waters are one of the waters crossed by the Indonesian Archipelago Sea Lane (ALKI) where large ships and tankers cross this water area. In the northern part of the Karawang Waters, there are also oil and gas drilling activities belonging to one of the national oil and gas companies, so there is a high risk of oil spill disasters. On April 22, 2021, there was an underwater oil pipeline leak around the oil well area operated by PT Pertamina Hulu Energi Offshore North West Java (PHE ONWJ). This study aims to analyze the distribution of oil spills using the Sentinel 1A Synthetic Aperture Radar (SAR). The research location includes the Karawang Waters where there has been an oil spill case. The method used to detect oil spills from Sentinel-1A satellite imagery is the adaptive threshold. The stages carried out for satellite image processing are image correction such as radiometric calibration, multilooking, filtering and dark spot detection using an adaptive threshold. Wind direction and speed data are used to see the movement of the oil spill area. The results of the study show that SAR Sentinel 1A imagery provides good enough information to detect oil spills and their distribution in the waters north of Karawang.